Enablers of enterprise systems training success – an exploratory investigation. (8th January 2007) - Rajagopalan, Balaji; York, Kenneth M.; Doane, David P.; Tanniru, Mohan
Enterprise systems are critical to organisational success and training is a critical factor for their successful implementation. With over US$84 billion invested in these systems, implementation failures can be disastrous for organisations. There is a growing realisation that, despite being touted as being critical to implementation, training is usually under-funded and scant attention is paid to designing training programmes. This exploratory study examines six training enablers that impact training success in the context of an Enterprise Resource Planning (ERP) implementation at a Fortune 500 organisation. We find evidence that the set of six training enablers are predictive of training success as measured by user satisfaction with training and training effectiveness. Implications of our study for researchers and the practitioner community as well as the limitations of our study and issues for future research are discussed.